Pengaruh Kesadaran Wajib Pajak, Pengetahuan Perpajakan dan Kualitas Pelayanan Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor di Kabupaten Sukoharjo - Wahyu Dwi Handayani; Hadi Samanto; Sri Laksmi Pardanawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The research aims to determine the effect of taxpayer awareness, tax knowledge and service quality on motor vehicle taxpayer compliance in Sukoharjo Regency (Case Study at Samsat Sukoharjo). This study uses a quantitative approach using primary data obtained from distributing questionnaires to respondents. Research indicators are arranged based on a Likert scale to measure the variables studied. The population in this study were motor vehicle taxpayers registered at the Regional Revenue Management Unit (UPPD) Samsat Sukoharjo Regency. Sampling was carried out using a simple random sampling technique with a sample size of 100 respondents. Consisting of 25 respondents who filled out the printed questionnaire directly and 75 respondents who filled out the questionnaire online via Google Form. The collected data were processed using IBM SPSS version 23 software using descriptive statistical analysis methods, validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, F tests, t tests and coefficients of determination. The results showed that the variables of taxpayer awareness and tax knowledge had a positive and significant effect on motor vehicle taxpayer compliance in Sukoharjo Regency. Meanwhile, the service quality variable has a negative and significant effect on motor vehicle taxpayer compliance in Sukoharjo Regency.